The Impact of Work Life Quality, Organizational Commitment and Satisfaction on Employee Performance at PT. Suzuki Finance Indonesia Makassar City - Muhammad Hamka; Andi Jam’an; Maklassa Maklassa (Eduvest - Journal of Universal Studies, 2025)
This research focuses on three main variables that are assumed to have an influence on employee performance, namely, Quality of Work Life, Organizational Commitment and Job Satisfaction. These three factors are analyzed to see their influence on employee performance, which is an important indicator in the effectiveness and productivity of the company, especially at PT Suzuki Finance Indonesia Makassar branch. This research is quantitative, involving 34 respondents. Questionnaires were used for data collection, which were then analyzed using Multiple Linear Regression Analysis on the SPSS Version 23 application. The results of this study indicate that quality of work life, organizational commitment, and job satisfaction each have a positive and significant influence on employee performance. These findings indicate that a supportive work environment, a sense of belonging to the company, and satisfaction with various aspects of work (such as salary, relationships with superiors, and development opportunities) play an important role in driving employee productivity and effectiveness. All three are not only directly related, but also statistically proven to make a real contribution to improving performance, which means companies need to pay attention to these factors in human resource management strategies.